Blood vessels as a scaffold for neuronal migration. (June 2019) - Fujioka, Teppei; Kaneko, Naoko; Sawamoto, Kazunobu
Abstract: Neurogenesis and angiogenesis share regulatory factors that contribute to the formation of vascular networks and neuronal circuits in the brain. While crosstalk mechanisms between neural stem cells (NSCs) and the vasculature have been extensively investigated, recent studies have provided evidence that blood vessels also play an essential role in neuronal migration in the brain during development and regeneration. The mechanisms of the neuronal migration along blood vessels, referred to as "vascular-guided migration, " are now being elucidated. The vascular endothelial cells secrete soluble factors that attract and promote neuronal migration in collaboration with astrocytes that enwrap the blood vessels. In addition, especially in the adult brain, the blood vessels serve as a migration scaffold for adult-born immature neurons generated in the ventricular-subventricular zone (V-SVZ), a germinal zone surrounding the lateral ventricles. The V-SVZ-derived immature neurons use the vascular scaffold to assist their migration toward an injured area after ischemic stroke, and contribute to neuronal regeneration. Here we review the current knowledge about the role of vasculature in neuronal migration and the molecular mechanisms controlling this process. While most of this research has been done in rodents, a comprehensive understanding of vasculature-guided neuronal migration could contribute to new therapeutic approaches for increasing new neurons in the brain after injury. Highlights: Neuroblasts migrate along vasculature in the developing and adult brain. Brain vasculature provides a scaffold and soluble factors for migrating neuroblasts. Brain vasculature supports neuroblast migration toward a lesion after stroke.